Low Power He:Ne Laser Radiation in Killing Photosensitized Helicobacter pylori in Vitro - Kandela, Siham A.; Melconian, Alice K.; Bakkour, Suzanne M. (Iraqi Journal of Laser, 2004)
Four photosensitizers were used to test inhibitory effect of Helicobacter pylori bacteria usinglow power helium: neon red laser radiation. Biopsies were collected from 176 patients and H. pylori wereisolated, identified and bacterial suspension was prepared. Samples of this suspension were mixed withvarious low concentrations of the test sensitizer. The mixture samples were exposed to different laserradiation doses. The samples were then inoculated and the inhibition zones were studied and comparedwith their analogues of control samples. The most effective sensitizer with optimum concentration andirradiation dose was determined. Statistical analysis of results was performed. The sensitizers' toluidineblue and the methylene blue with concentration of 100 mg/ml were able to produce the same effect ofcomplete killing when irradiation energy density 13 J/cm2. However, thionin and crystal violet sensitizerswhen used with the same concentration and exposed to the same laser dose, showed minor inhibitoryeffect. Irradiation of bacterial samples with absence of sensitizer or sensitized samples at theconcentrations employed with out laser radiation has no effect on H. pylori viability in all of theexperiments.